The variety of spring soft wheat ‘Tulaykovskaya 108’ - V. V. Syukov; A. A. Viyushkov; S. E. Porotkin (Зерновое хозяйство России)
The article presents the technology of development of the variety of spring soft wheat ‘Tulaykovskaya 108’. In the selection process we have managed realizing the tasks appeared in the selection of parental forms. We have managed combining productivity, drought tolerance of the variety ‘Lyutestsens 1222’ with productivity, resistance to lodging and good baking properties of the variety ‘Tulaykovskaya Belozernaya’. Besides, we have realized the planned transgressions in tolerance to brown rust and powdery mildew. The variety ‘Tulaykovskaya 108’ is characterized with high and stable productivity. In the years 2012-2014 the average yields of ‘Tulaykovskaya 108’on five plots of the Samara region was 2.17 t/ha, that is on 0.37 t/ha more than the yields of ‘Kinelskaya Niva’ and on 0.29 t/ha more than the yields of ‘Tulaykovskaya 10’. The variety surpassed the standard varieties on the plots of the Penza, Orenburg regions, of the Republics of Bashkortostan, Mordoviya and Tatarstan. The largest yields were obtained in 2012 on the Buinsk SVP of the Republic of Tatarstan (5.5 t/ha or 0.6 t/ha more than of ‘Simbirtsit’).